Narratives in specialist palliative medicine. Issue 2 (30th November 2007) - Malthouse, M
Abstract : Where modern medicine has been criticised for having lost sight of the individual on account of its biomedical focus, the profile of narrative in medicine has gained prominence. Within any medical encounter it is possible to identify the existence of several narratives. The aim of this article is to demonstrate this characteristic within the context of specialist palliative care. The emphasis is to see how an awareness of these narratives might improve upon how we attend to the suffering of dying patients. A narrative approach to this work could also help doctors and other healthcare professionals find meaning and understanding in themselves while working in an environment of death and dying. This can expose many challenging personal dimensions that demand reflection, possibly through narrative. The nature of the narratives identified is such that they can weave together and interlink into a greater whole to achieve a much wider set of meanings and shared understandings. However, they can exist in a fragmented state, in which ambiguity, uncertainty and incoherence are sustained. The effect of this should be to encourage us to engage in a more active process of finding meaning, and certainly to recognise that there could be more than one reading or interpretation.